A Predictable Aesthetic Rehabilitation of Deciduous Anterior Teeth in Early Childhood Caries - Priyanka Agarwal; Rashmi Nayak; Ghayathri Elangovan (Case Reports in Dentistry)
Aesthetic dentistry plays a significant role not only in adults but also in pediatric patients. However, a pediatric dentist is faced with the dual problem of satisfying the aesthetic expectations of the patient and parents as well as managing the pediatric patient. In the present era, there are numerous restorative techniques that can be applied to different clinical scenarios. However, we have to choose the technique that best suits our patient, not only biologically but also aesthetically, psychologically, functionally, and financially. The following paper presents the clinical sequence of rehabilitation of severely carious maxillary anterior teeth from left to right lateral incisors in a child with early childhood caries. Severely carious anterior teeth were endodontically treated. The central incisors were restored with gamma loop posts which is mainly used for pediatric patients in endodontically treated teeth. Lateral incisors were treated with Ribbond polyethylene fibre posts. Following this, all the teeth were restored aesthetically with free-hand composite buildup after proper shade selection. The occlusion was restored, and the restorations were finished and polished.